Penerapan Breathing Relaxation Balloon Blowing sebagai Intervensi Keperawatan untuk Meningkatkan Saturasi Oksigen pada Pasien Tuberkulosis: Case Report - Mohammad Dwi Ardianto; Shalsa Nabilla (JURNAL KESEHATAN KARTIKA, 2026)
Background: Tuberculosis (TB) remains a global health issue with high incidence rates in Indonesia, including West Java Province. Patients with pulmonary TB often experience abnormal breathing patterns that lead to decreased oxygen saturation. Non-pharmacological interventions are needed as complementary therapies to help improve respiratory function. The balloon-blowing breathing relaxation technique is a breathing exercise aimed at improving lung expansion and gas exchange efficiency through the mechanism of positive expiratory pressure. Objective: To describe the application of the balloon-blowing breathing relaxation technique as a nursing intervention to improve oxygen saturation in patients with pulmonary TB. Methods: A descriptive approach using the case report method, covering the nursing care process from assessment to evaluation. The study subject was Mr. J (70 years old) with a medical diagnosis of pulmonary tuberculosis in the Lavender Ward of X General Hospital. The intervention was administered once daily for 15 minutes over three consecutive days. Oxygen saturation measurements were taken using a pulse oximeter before and after the intervention. Results: There was a gradual increase in oxygen saturation from 93% on the first day to 98% on the third day following the intervention. The patient also reported a reduction in shortness of breath and appeared more relaxed. The nursing problem of ineffective breathing pattern was resolved after three days of intervention. Conclusion: The balloon-blowing breathing relaxation technique proved effective as a self-care nursing intervention in improving oxygen saturation in patients with pulmonary tuberculosis. This intervention can be recommended as a complementary therapy in clinical nursing practice to support improvements in patients’ oxygenation status.